Impact of exclusive breastfeeding on physical growth - Sitelbanat Osman Mohamed Ahmed; Hawa Ibrahim Abdalla Hamid; Aruna Jothi Shanmugam; Murtada Mustafa Gabir Tia; Soad Mohamed Abdalla Alnassry (Clinical Nutrition Open Science, 2023)
Summary: Background: Breastfeeding is considered the gold standard in infant feeding, as it provides ideal nutrition for infants. Both the World Health Organization (2016) and the American Academy of Pediatrics (2012) recommend exclusive breastfeeding from birth until 6 months of life.Aim: To investigate the association between exclusive breastfeeding and infant growth, as measured by weight, height, and head circumference compared with the growth chart. Materials and Methods: A cross-sectional retrospective community-based study was conducted in a primary health care facility (Maternity and Child Care Center) in Shendi, River Nile State, Sudan. Data were collected from 103 healthy infants with exclusive breastfeeding who attended the maternity and child care center using anthropometric measurements and compared to the Centers for Disease Control and Prevention growth chart. Results: The current study found that most (96.2%) of exclusively breastfed infants weighed within the normal range of the growth chart between the 10th and 90th percentile and that breastfeeding affected average height since all exclusively breastfed infants were within normal height ranges. Exclusive breastfeeding however did not affect head circumference. Conclusions: There was a significant impact of exclusive breastfeeding on the weight and height of infants, but never on head circumference. These findings support the current World Health Organization (WHO), American Academy of Pediatrics, and United Nations International Children's Emergency Fund (UNICEF) recommendation for exclusive breastfeeding during the first 6 months of life as a key to healthy growth and development.